Tradisi Maddoja Bine Dalam Peningkatan Kualitas Padi Terhadap Jual Beli Gabah Perpektif Fiqih Muamalah (Studi Kasus di Takkalasi Kabupaten Barru) - Armila; Rahmawati; Saidah (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2024)
This thesis examines the review of al-muāmalah al-adabiyah in the transactions of buying and selling bricks in Amassangan Village, Binuang District, Polewali Mandar Regency. The aim of this research is to describe the practice of buying and selling bricks in Amassangan Village, Binuang District, Polewali Mandar Regency, and to analyze the application of al-muāmalah al-adabiyah in the transactions of buying and selling bricks in Amassangan Village, Binuang District, Polewali Mandar Regency. The research questions are (1) what are the practices of buying and selling bricks in Amassangan Village, Binuang District, Polewali Mandar Regency? (2) how is al-muāmalah al-adabiyah applied in the transactions of buying and selling bricks in Amassangan Village, Binuang District, Polewali Mandar Regency? The type of research used is field research with qualitative methods, employing a normative approach. Data collection techniques include observation, interviews, and documentation, while data analysis involves identifying data, presenting data, and drawing conclusions. The research findings indicate that the practice of buying and selling bricks in Amassangan Village, Binuang District, Polewali Mandar Regency is deemed lawful according to Islamic law as the conditions and pillars of the transaction have been fulfilled. Considering that the principles of al-muāmalah al-adabiyah have been applied in the practice of buying and selling bricks in Amassangan Village, Binuang District, Polewali Mandar Regency, it is recommended that buyers exercise caution and diligence in all transactions, particularly in purchase agreements, by documenting the agreed-upon terms. This approach ensures that transactions result in mutual benefits and contribute to the establishment of an economic environment based on the principles of al-muāmalah al-adabiyah, fostering mutual assistance and the promotion of a thriving economic livelihood.